2008
DOI: 10.1161/hypertensionaha.108.114058
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Angiotensin II Type 2 Receptor Mechanisms Mediate Decreases in Arterial Pressure Attributable to Chronic Low-Dose Angiotensin II in Female Rats

Abstract: Abstract-The renin-angiotensin system is a far more complex enzymatic cascade than realized previously. Mounting evidence suggests sex-specific differences in the regulation of the renin-angiotensin system and arterial pressure. We examined the hemodynamic responses, angiotensin II receptor subtypes, and angiotensin-converting enzyme 2 gene expression levels after graded doses of angiotensin II in males and females. Mean arterial pressure was measured via telemetry in male and female rats in response to a 2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
148
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(166 citation statements)
references
References 35 publications
15
148
3
Order By: Relevance
“…Our finding is in agreement with previous works showing that hypertension induced by AngII is lower in female than in male mice 40, 41. The protective effect of 17β‐estradiol is, at least in part, mediated by the AngII type 2 receptor 42.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is in agreement with previous works showing that hypertension induced by AngII is lower in female than in male mice 40, 41. The protective effect of 17β‐estradiol is, at least in part, mediated by the AngII type 2 receptor 42.…”
Section: Discussionsupporting
confidence: 93%
“…[5][6][7][8] Recently, with the discovery of angiotensin-converting enzyme 2, a depressor axis to the RAS has been identified 9 that incorporates the angiotensin type 2 receptor (AT 2 R), which is upregulated by estrogen. 7,10 Previously, we have demonstrated that the vasodepressor RAS pathways are enhanced in females and that the AT 2 R has a depressor influence on the response to chronic angiotensin II (Ang II) infusion in female but not in male rats.…”
mentioning
confidence: 99%
“…7,10 Previously, we have demonstrated that the vasodepressor RAS pathways are enhanced in females and that the AT 2 R has a depressor influence on the response to chronic angiotensin II (Ang II) infusion in female but not in male rats. 5 Estrogen also has been shown to protect against Ang IIinduced hypertension in female mice, suggesting the importance of the interaction between estrogen and the RAS in this response in females. 6,11 Thus, the AT 2 R appears to play a role in countering the pressor actions of Ang II at the angiotensin type 1 receptor (AT 1 R) in females via an estrogen-dependent mechanism and may contribute to gender differences in arterial pressure control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also consistent with the effects of RapLo binding of EGF pathways are the observations that infusions of low dose angiotensin II stimulate AT2r to decrease arterial pressure in normal animals. The effect is expressed and enhanced in the presence of estrogens and is opposed by androgens [48].…”
Section: Receptor Independent Actions Of Egfmentioning
confidence: 98%